The Effect of Implementing A Project-Based Learning Model on Critical Thinking Skills - Fince Putra Jaya Zalukhu; Yanida Bulolo; Mei Siska Putri Mendrofa; Pasrah Eli Hulu (Journal of Social Science Utilizing Technology, 2024)
Background. 21st-century education demands the enhancement of critical thinking skills to face global challenges and technological advancements. One effective method is project-based learning (PBL), which involves students in complex projects to encourage exploration and real-world application of knowledge. This study aims to determine the effect of PBL on students' critical thinking skills, considering many students still struggle to analyze information critically. With PBL, students are expected to be more active and critical in learning. This research is important for improving the quality of education and serves as a foundation for developing innovative learning strategies. Purpose. This research was conducted to determine the application of project-based learning to critical skills. Method. The type of research carried out is Classroom Action Research. This research is more about describing data, facts and conditions in th  field using three stages. The data collection techniques used are: tests, observations, interviews and documentation. The data analysis used in this research is qualitative descriptive analysis. Results. Hasil penelitian ini menunjukan urutan keterampilan berpikir kritis untuk kelompok MPL setelah pembelajaran, nilai rata-rata yang diperoleh dalam komponen penjelasan adalah dengan skor rata-rata 42,53 dalam kategori kurang. Nilai rata-rata tertinggi diperoleh pada komponen interpretasi dengan nilai rata-rata 52,41. Hal ini menunjukkan bahwa kelompok MPL lebih mampu dalam memahami dan menyatakan makna atau signifikansi dari pengalaman, situasi, data, penilaian, prosedur, atau kriteriats. Conclusion. Kesimpulan penelitian ini adalah sebagai berikut. Pertama, terdapat perbedaan keterampilan berpikir kritis antara kelompok siswa yang belajar dengan model pembelajaran berbasis proyek dan model pembelajaran langsung. Kedua, terdapat perbedaan signifikan pada variabel model pembelajaran terhadap keterampilan berpikir kritis. Ketiga, terdapat perbedaan signifikan pada variabel model pembelajaran terhadap keterampilan berpikir kritis.